The Financial Contribution Of Households Using By Health Services - Mehdi Yousefi; Abbas Assari Arani; Bahram Sahabi; Anushiravan Kazemnejad; Somayeh Fazaeli (Tehran University of Medical Sciences, 2015)
Background and Aim: The Household financial contribution is one of the most important issues in health system. This study aims to determine and present some indices of h ousehold financial contribution in health system in Iran. Materials and Methods: In this cross sectional- descriptive study, the methods were introduced by World Health Organization. Fair Financing Contribution Index (FFCI), catastrophic health expenditure and impoverishment in Iran were calculated from a national representative data derived from Iranian Statistics Center, Household Budget Survey, and Consumption Expenditures, at 2011. The indicators have been calculated on the basis of the total cost analysis, health and capacity to pay Iranians households. Results: Household financial contribution in the health system for households living in rural areas is more than urban areas. In this study, more than 3 percent of the households were facing catastrophic health expenditure . Also 1.5 percent of the households have been impoverished. Fair Financing Contribution Index in rural and urban areas was 59 and 65 percent respectively. Conclusion: Calculation of the indicators related to households financial contribution in Iranian health system need to predict and implement appropriate plans, as well as monitoring and assessment of health system programs in order to increase the equity in the household financial contribution and effectiveness of Utilization of resources.